Truth commissions: Memory, power, and legitimacy (In Factis Pax: Journal of Peace Education and Social Justice, 2018)
Truth commissions: Memory, power, and legitimacy, by Onur Bakiner, Philadelphia, University of Pennsylvania Press, 2016, pp. vi+315, $65.00 (hardcover), ISBN: 978-0-8122-4762-6.